2022
DOI: 10.3389/fnut.2022.824525
|View full text |Cite
|
Sign up to set email alerts
|

Antifatigue Effect of Panax Notoginseng Leaves Fermented With Microorganisms: In-vitro and In-vivo Evaluation

Abstract: Fatigue is a common physiological phenomenon caused by many complicated factors. Excessive fatigue will lead to a series of uncomfortable reactions and damage body health. Panax notoginseng leaves (PNL) is a new resource food that good for soothing nerves, nourishing the heart, and strengthening the spleen. Microbial fermentation could increase the content of bio-ingredients and produce new active ingredients. However, the effect of fermented P. notoginseng leaves (FPNL) on antifatigue and the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Therefore, the SLPN-instant beverage manufactured from SLPN is rich in total saponins, polyphenols, ginsenosides and nutrition, shows a good antioxidation and might be neuroprotective in neurological disorders. Previous reports indicated that fermented SLPN increased liver glycogen and serum lactate dehydrogenase activity, decreased blood urea nitrogen, lactate acid, and malondialdehyde in mice, showed a good antifatigue effect and in vivo ( 45 ). SLPN saponins could inhibit abnormal autophagy and produce cardioprotective effects in mice ( 42 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the SLPN-instant beverage manufactured from SLPN is rich in total saponins, polyphenols, ginsenosides and nutrition, shows a good antioxidation and might be neuroprotective in neurological disorders. Previous reports indicated that fermented SLPN increased liver glycogen and serum lactate dehydrogenase activity, decreased blood urea nitrogen, lactate acid, and malondialdehyde in mice, showed a good antifatigue effect and in vivo ( 45 ). SLPN saponins could inhibit abnormal autophagy and produce cardioprotective effects in mice ( 42 ).…”
Section: Discussionmentioning
confidence: 95%
“…The total saponin of SLPN could activate the PI3K/Akt/mTOR signaling pathway to attenuate excessive autophagy and apoptosis in myocardial cells in heart tissue induced by sleep deprivation ( 42 ). Furthermore, fermented P. notoginseng leaves could increase the content of secondary metabolites, and show a good antifatigue effect in vivo and in vitro ( 45 ), and the ethanol-induced metabolic perturbations are restored when treated by SLPN saponin ( 42 ). In our experiment, forty-three triterpenoid ginsenosides were identified in SLPN by UPLC-MS ( Supplementary Table 1 , Supplementary Figure 2A ).…”
Section: Discussionmentioning
confidence: 99%
“…The end‐product of anaerobic glycolysis (Yang et al., 2022 ), BLA accumulates during high‐intensity physical labor and inhibits muscle contraction to induce fatigue (Zhao et al., 2018 ). Thus, BLA is a crucial index of postexercise fatigue (Surhio et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Excess ROS breaks down polyunsaturated fatty acids to cause lipid peroxidation, producing MDA as a by‐product (Qi et al., 2014 ; Yang et al., 2014 , 2015 ; Zhou et al., 2022 ). Thus, fatigue increases MDA levels (Yang et al., 2022 ; Zhao et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…It reveals that the pleasure experienced by both boys and girls increases after implementing two mixed units each week. However, when the exercise frequency is excessive, insu cient time for rest and recovery in children and adolescents may make lactic acid accumulate in the muscles and cause physical exhaustion (71,72). There is a detrimental impact on the individual's continuous engagement in physical exercises (73).…”
Section: Analysis Of Frequencymentioning
confidence: 99%